2023
DOI: 10.3390/pharmaceutics15071985
|View full text |Cite
|
Sign up to set email alerts
|

Development of Atomoxetine-Loaded NLC In Situ Gel for Nose-to-Brain Delivery: Optimization, In Vitro, and Preclinical Evaluation

Dibyalochan Mohanty,
Omar Awad Alsaidan,
Ameeduzzafar Zafar
et al.

Abstract: The present study investigates the brain-targeted efficiency of atomoxetine (AXT)-loaded nanostructured lipid carrier (NLC)-laden thermosensitive in situ gel after intranasal administration. AXT-NLC was prepared by the melt emulsification ultrasonication method and optimized using the Box–Behnken design (BBD). The optimized formulation (AXT-NLC) exhibited particle size PDI, zeta potential, and entrapment efficiency (EE) of 108 nm, 0.271, −42.3 mV, and 84.12%, respectively. The morphology of AXT-NLC was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Among the ways of application of colloidal systems based on solid lipids extensively documented in the literature are cosmetic [5,8,9], food [4,6,10], and, above all, in the pharmaceutical industry (i.e., drug delivery) [7,11,12]. In recent years, lipid formulations have enabled the effective encapsulation of active substances successfully delivered intravenously [13][14][15], orally [16][17][18], transdermally [19][20][21], and also directly into the eye [22][23][24] or nose [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Among the ways of application of colloidal systems based on solid lipids extensively documented in the literature are cosmetic [5,8,9], food [4,6,10], and, above all, in the pharmaceutical industry (i.e., drug delivery) [7,11,12]. In recent years, lipid formulations have enabled the effective encapsulation of active substances successfully delivered intravenously [13][14][15], orally [16][17][18], transdermally [19][20][21], and also directly into the eye [22][23][24] or nose [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Teaima and coworkers prepared solid lipid nanoparticles for the brain targeting of ATMH and sustained the release of ATMH for 8 h [6]. Mohanty et al (2023) prepared ATMH-loaded nanostructured lipid carriers and demonstrated the sustained release of ATMH for 12 h [7]. Similarly, Stanojevic and coworkers prepared tablets for the sustained release of ATMH of up to 8 h [8].…”
Section: Introductionmentioning
confidence: 99%